The household practices by women civil servants and waste generation in Osun State, Nigeria - Oyegoke, Bolatumi (Penerbit Universiti Kebangsaan Malaysia, 2022)
The polluted and degraded condition of the environment in Osun State, Nigeria was attributed to poor waste management practices of women who are responsible for 90% of household activities. Women civil servants who are educated but earn meager salaries, they are also positioned to influence policies and are not exempted from the poor waste management practices. These women, in carrying out their role as the primary care giver engaged in household activities and service-oriented activities. These activities generate huge amount of waste materials in solid, liquid and gaseous forms and are poorly disposed as inputs into the environment. Poorly disposed waste materials are threats to environmental sustainability in many ways. Therefore, this study was conducted to establish the household waste generating practices of women civil servants in Osun State. Also, ways by which these women disposed their wastes were also discussed. The study was guided by the environmental citizenship theory. Within the qualitative research method, the phenomenological design was employed to carry out the study. Purposive sampling technique was used at the various stages of the multistage sampling. Data was collected by conducting interviews using semi structured and open ended questionnaires as instruments as well as observation. A total of 19 female civil servants participated in the study. The study concluded with the findings that, the household practices of women involve generation of huge amount of waste that are poorly stored, irregularly collected and poorly disposed. The paper recommends knowledge of environmental issues such as the impact of poor waste management on the environment, good waste management practices and the practice of environmentally friendly economic activities as ways of improving the condition of the environment in the State.